Therapie von Lebererkrankungen bei Haustieren mit Chelidonium majus - Kirkilessi, Georgia; Loukaki, Katerina (Zeitschrift für Ganzheitliche Tiermedizin, 2007)
Eight dogs and two cats expressing symptoms of liver dysfunction caused by various agents have been presented in our clinic. After biochemical examination of sera the liver dysfunction was verified. After informing the owner a homeopathic treatment was administered. One capsule of the homeopathic remedy Chelidonium majus 30 CH was given p. o. once or twice depending on the different cases. An improvement of clinical signs and or biochemical values was noticed in both species and in most of the cases. Animals can tolerate and respond in a better way to further causative treatment of the hepatic disorder (conventional and/or alternative). A possible explanation could be that Chelidonium majus stimulates the regeneration of the liver and reinforces its function. Further research is needed to investigate the efficacy of Chelidonium majus in comparison and in combination with the idiosyncratic (constitutional) homeopathic remedy, the efficacy of lower and higher potencies, the combination of its use together with special diets and other conventional or/and alternative therapeutic methods.
Keywords: Homeopathy; Chelidonium majus; liver diseases; hepatic disorders; dogs; cats